2015
DOI: 10.3174/ajnr.a4333
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Necrosis in Pediatric Patients with Brain Tumors Treated with Proton Radiotherapy

Abstract: BACKGROUND AND PURPOSE:Proton radiotherapy has been increasingly utilized to treat pediatric brain tumors, however, limited information exists regarding radiation necrosis among these patients. Our aim was to evaluate the incidence, timing, clinical significance, risk factors, and imaging patterns of radiation necrosis in pediatric patients with brain tumors treated with proton radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(68 citation statements)
references
References 22 publications
1
65
0
2
Order By: Relevance
“…In addition to a more accurate dose calculation, the MC calculation allows the inclusion of a relative biological effectiveness (RBE) model based on the dose-weighted linear energy transfer (LETd) of the protons [10]. This was deemed valuable given the uncertainty [11,12] of the proton RBE as a function of linear energy transfer (LET), the complexity of IMPT plans, and the recent reports of necrosis following PBT [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to a more accurate dose calculation, the MC calculation allows the inclusion of a relative biological effectiveness (RBE) model based on the dose-weighted linear energy transfer (LETd) of the protons [10]. This was deemed valuable given the uncertainty [11,12] of the proton RBE as a function of linear energy transfer (LET), the complexity of IMPT plans, and the recent reports of necrosis following PBT [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical reports on the harms of PT have been published previously, 60,61 including the possibility of increased acute brain injury with use of PBT in children 62 with a high (31%) incidence of rates of radiation necrosis occurring in multiple areas in the brain remote to the initial tumour site and with a short time to onset. 60 Gunther et al reported more frequent MRI changes with PBT compared to IMRT for paediatric ependymoma. 20 There were higher rates of neurological adverse effects in the systematic review by Patel et al 12 in patients with paranasal sinus tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Several papers have identified this as a potential problem in proton therapy, specifically more brain necrosis than expected. This may be due to the RBE in normal brain for protons being higher than 1.1, which is likely only more probable if using carbon ions and a SOBP.…”
Section: Opening Statementsmentioning
confidence: 99%